PWE-086 Determining Stem Cell And Crypt Dynamics In Inflammatory Bowel Disease. (9th June 2014) - Jawad, N; Crook, J; Baker, A-M; Cereser, B; Rodriguez-Justo, M; Graham, T; Wright, N; McDonald, S
Abstract : Introduction: Inflammatory bowel disease (IBD) confers a high risk of development of colitis-associated colorectal cancer (CACRC) in patients with extensive colitis. It is believed that a field effect, resulting from chronic inflammation and clonal outgrowth is present in ulcerative colitis (UC) patients, and this promotes the accumulation of protumourigenic clones via increased crypt fission rates. Increased rates of crypt fission may explain the mass expansion of protumourigenic mutations across the whole length of the bowel in a very short time period as observed in patients with CACRC (Leedham et al ., 2009; Galandiuk et al ., 2012). Methods: Fresh frozen normal colon (n = 15) and UC colon (n = 6) tissue samples were collected and sectioned in an en face orientation. Two-colour enzyme histochemistry for cytochrome c oxidase (CCO) activity was performed to identify clonal populations. Adjacent crypts completely deficient of CCO activity were recorded as a 'CCO deficient patch' and those with a fraction of the crypt that was CCO-deficient were designated as 'partial crypts'. The CCO-deficient clone fraction in partial crypts was estimated by recording the number of pixels within CCO-deficient (blue) and CCO-proficient (brown) areas. The number and size of clonal patches in colitis patients was compared to non-UC controls. Results: As in the healthy colon, CCO-deficient clonal patches accumulate in an age dependent fashion in the UC colon. The mean number of crypts within a CCO-deficient patch was statistically significantly larger (p < 0.05) in the UC colon than in the normal colon. In addition we observe a larger percentage of wholly and partially CCO-deficient crypts in the UC colon when compared to the normal controls. Conclusion: The proliferative drive induced by continuous inflammation and mucosal repair in UC appears to promote the expansion of CCO-deficient patches. The increase in the proportion of wholly and partially mutated crypts in UC could be explained by crypt hyperplasia with more stem cells present driving fission. This increased rate of clonal expansion may contribute to the increased rate of tumorigenesis in the colitic bowel, however analysis of a larger patient cohort is needed. References: 1 Leedham SJ, Graham TA, Oukrif D, McDonald SA, Rodriguez-Justo M, Harrison RF, Shepherd NA, Novelli MR, Jankowski JA, Wright NA. Clonality, founder mutations and field cancerization in human ulcerative colitis-associated neoplasia. Gastroenterology 2009 Feb;136(2):542-50 2 Galandiuk S, Rodriguez-Justo M, Jeffery R, Nicholson AM, Cheng Y, Oukrif D, Elia G, Leedham SJ, McDonald SA, Wright NA, Graham TA. Field cancerization in the intestinal epithelium of patients with Crohn's ileocolitis. Gastroenterology 2012 Apr;142(4):855 Disclosure of Interest: None Declared.